HIPONIMI DALAM TERJEMAHAN MAULID DIBA’ KARYA ACHMAD SUNARTO - Ahmad Riza Fauzi; Sumarlam Sumarlam (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2021)
Hyponymy is one of the studies in lexical discourse. Translation as a linguistic product certainly has various perspectives in language studies, for example, the study of hyponymy in the translation of maulid diba'. Maulid diba 'is a book of poetry that is well-known among the Muslim community in Indonesia and the world. This book contains the life history of the prophet and after it, therefore it is assumed that there is hyponymy in the translation of the text. This study discusses the hyponymy in the translation of Maulid diba' by Achmad Sunarto and its context. This research is a qualitative descriptive study. The data collection method used in this research is the listen and note method. The data analysis method uses the matching method and the agih method. The source of data in this study is the book Translation of Maulid Diba' by Achmad Sunarto published by Thulus Harapan, in the city of Surabaya in 2016. Finally, the results of this study found seven categories of hyponymy, namely 1) hyponymy category of the characteristics of Rasululah, 2) hyponymy of the attributes of Allah, 3) hyponymy of human anatomy (the majesty of Allah), 4) hyponymy of human anatomy (attributes of the Prophet), 5) hyponymy of the names of the prophets, 6) hyponymy of the solar system, and 7) the names of animals.Keywords: hyponymy, translation of maulid diba', Achmad Sunarto